Thyroid Follicles and Parenchyma are Found to Increase with Advancing age during the first 50 years of life in Bangladeshi People - Nurunnabi, Abu Sadat Mohammad; Mahbub, Sabiha; Shahriah, Sunjida; Begum, Gul Newaz; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2010)
Background: The structural components of the thyroid gland are very much responsive to many types of stimuli and their adaptation is evident in histological studies. The thyroid follicles change their size and shape with the physiological alterations and pathological deviations. Objective: To observe the histological changes of the thyroid gland with advancing age in Bangladeshi people. Methods: This cross-sectional study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka from January to December 2008. The present study was performed on 60 post mortem human thyroid gland (39 of male and 21 of female) collected from unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into three age-groups including Group A (10 - 20 years), Group B (21 - 50 years) & Group C (> 50 years) and the glands were studied histologically including number and average diameter of the thyroid follicles, percentage proportion of the parenchyma and stroma. Results and conclusion: All the histological values of the thyroid gland studied i.e. number and average diameter of the thyroid follicles and percentage of the parenchyma, are found to increase with advancing age during the first 50 years of life and later decrease. Key Words: Thyroid gland, Thyroid follicles, Parenchyma, Stroma DOI: 10.3329/jbsp.v4i2.4179 J Bangladesh Soc Physiol. 2009 Dec;4(2): 88-92